Graft polymerization of 4‐imidazole acrylic acid onto polyurethane for the improvement of water compatibility and antifungal activity. Issue 11 (2nd February 2018) - Chung, Yong‐Chan; Kim, Ha Youn; Choi, Jae Won; Chun, Byoung Chul
Abstract : The graft polymerization of 4‐imidazole acrylic acid (IA) onto polyurethane (PU) was conducted to prepare antifungal PU with enhanced water compatibilities. Poly(IA) chains with different IA content were grafted onto PU in an IA series, whereas they were not grafted onto PU in a control CIA series. The carboxyl contents of the IA and CIA series, as determined by acid/base titration, proportionally increased with an increase in the IA feed, but the water contact angles of only the IA series significantly decreased compared with those of the CIA series and plain PU. The maximum tensile stress of the IA series sharply increased because of the chemical linking of the grafted poly(IA) chains, whereas the tensile strain at break was not affected by the grafted poly(IA) chains. The shape recovery of the IA series at 10°C notably improved with the grafting of poly(IA) chains, whereas that of the CIA series did not increase at all. The IA series samples completely suppressed fungal growth on PU because of the grafted imidazole groups and hydrophilic carboxyl groups. POLYM. ENG. SCI., 58:2088–2097, 2018. © 2018 Society of Plastics Engineers